Changes in chemical and sensory characteristics of Chemlali extra‐virgin olive oil as depending on filtration. Issue 1 (27th June 2016) - Jabeur, Hazem; Zribi, Akram; Bouaziz, Mohamed
Abstract : The oil extracted from olive paste is a turbid and opalescent juice which contains impurities that can affect its quality. Before olive oil packaging, filtration has recently become a standard processing procedure in order to obtain more brilliant extra‐virgin olive oil (EVOO), maintain its quality, and extend its shelf life. In this research work, changes occurring in the concentrations of some minor compounds during industrial filtration of Chemlali EVOO were studied. The chemical parameters with sensorial quality were also determined. After the filtration of oil, a slight increase in quality parameters was noticed, along with a slight influence on the sensory scores. The adopted filtration system reduces the moisture contents. However, non‐filtered olive oil might be more stable. Nevertheless, the behavior of phenolic compounds during filtration differed for each family. Indeed, the secoiridoids are the most affected phenolic compounds during EVOO filtration. Their concentrations increase significantly ( p < 0.05) except the decarboxylated ligstroside aglycon decreases during this process. Practical applications: This work clearly demonstrates the usefulness of filtration process in the Chemlali EVOO treatment. After industrial‐scale filtration process, the analysis of individual concentration of phenolic compounds indicated that the concentrations of secoiridoids increased significantly ( p < 0.05) mainly 3, 4‐DHPEA‐EA. Besides, olive oil brilliance is achieved by eliminating vegetable water and suspended particles; thus extending final product shelf life. Extra‐virgin olive oil is a turbid colloidal dispersion. The most common technique used to clear the oil is filtration. During this process, quantitative and qualitative changes take place, especially on minor components. Abstract : Extra‐virgin olive oil is a turbid colloidal dispersion. The most common technique used to clear the oil is filtration. During this process, quantitative and qualitative changes take place, especially on minor components.